Engineering carbon dots with amplified peroxidase-mimetic activity for dual-modal colorimetric-photothermal sensing of organophosphorus and carbamate pesticides - Na Gao; Yajuan Zhao; Yuhan Huang; Yanke Zhou; Linlin Yang; Liguo Ji; Hao Zhu; Wenjie Ren; Guangjie He (Analytica Chimica Acta, 2026)

Response of air quality changes and spatio-temporal distribution characteristics on the energy development changes in China - Jinjian Xin; Hongpeng Chen; Baoliang Sun; Yanke Ji; Li Yan; Guozhong Feng (Environment, Development and Sustainability, 2025)

Ambient-dried biomass 3D porous aerogel with “brick-mortar-binder” structure for the determination and adsorption of Cr(VI) - Ji Li; Yanke Xi; Hong Shao; Qianli Ma; Xiangting Dong; Xiang Li (Chemical Engineering Journal, 2025)

Exploring of laccase-like nanozyme and membrane filters for efficient removal of tetracycline hydrochloride - Yun Wang; Dan Wang; Qixuan Mu; Yanke Zhai; Jun Hai; Yibing Ji; Ruijun Li (Chemical Engineering Journal, 2024)

Transfer and risk assessment of fipronil in laying hen tissues and eggs - Zhiwei Wang; Ziyan Du; Yanke Shi; Peipei Qi; Shanshan Di; Huiyu Zhao; Xiaofeng Ji; Chunbo Lu; Xinquan Wang (Science of The Total Environment, 2024)

Flood Wave Superposition Analysis Using Quantitative Matching Patterns of Peak Magnitude and Timing in Response to Climate Change - Qiumei Ma; Lihua Xiong; Chong-Yu Xu; Rongrong Li; Changming Ji; Yanke Zhang (Water Resources Management, 2021)

Spatiotemporal patterns of satellite precipitation extremes in the Xijiang River Basin: From statistical characterization to stochastic behaviour modelling - Qiumei Ma; Changming Ji; Lihua Xiong; Yi Wang; Chong‐Yu Xu; Yanke Zhang (International Journal of Climatology, 2021)
Given the threats from rainstorm events that have been intensified due to climate change, the investigation of heavy/extreme precipitation is attracting increasing attention. The investigation of extreme precipitation, with its restricted tools and data, is quite different from that of nonextreme precipitation. Satellite precipitation estimates (SPEs) are promising precipitation measurements due to fine spatial resolution. However, the spatiotemporal patterns of SPE extremes remain unclear. Therefore, this study attempted to systematically analyse the spatiotemporal patterns of extreme SPEs provided by the Tropical Rainfall Measurement Mission (TRMM) research product from statistical characterization to stochastic behaviour modelling. The statistical characterization was depicted using comprehensive extreme precipitation indices (EPIs), while the stochastic behaviour was modelled using the generalized Pareto distribution (GPD) to fit the ‘peak over threshold’ samples and employing the max‐stable process to fit the ‘block maximum’ samples (Max: annual 1‐day maximum, RX1day: monthly 1‐day maximum, and RX5day: monthly 5‐day maximum) of the TRMM data. The TRMM extremes were analysed across the Xijiang River Basin, China. The results of the statistical characterization revealed that compared with gauge precipitation, most TRMM EPIs were discovered to have higher temporal dynamic levels. Moreover, the spatial median of the return level for each return period derived from temporal TRMM extreme modelling with the GPD was lower than that from gauge extremes. The spatial dependence of Max in TRMM was weaker than that of either RX1day or RX5day, primarily due to different precipitation‐generating processes existing between two extreme events at annual scale compared with monthly scale. Each of the Max, RX1day, and RX5day in TRMM exhibited stronger spatial dependence than that in gauge extreme precipitation, maybe related to the area‐average‐based representation of the SPEs. These findings can enhance our insight into the spatiotemporal patterns of extreme satellite precipitation, which is beneficial for operational flood risk management.